Externalidades ambientales del cableado aéreo: impacto y perspectivas de sostenibilidad urbana en Iquitos, Loreto – 2023 - Rodriguez Collantes, Michelle Nahomi (2024)
It is a non-experimental study of the descriptive, exploratory, cross-sectional type. The structured interview was used with a Cronbach's Alpha coefficient of 0.719 in the sites where a greater presence of overhead wiring is seen with a sample size of twenty five (25) interviews in an intentional sampling aimed at residents who carry out their daily activities. The Shapiro Wilk test was used, reporting that the data do not show significant deviations from a normal distribution, so the “t” test was used, which allowed us to conclude that the overhead wiring in Iquitos generates significant environmental externalities, such as visual pollution, impact on biodiversity, and fragmentation of the natural landscape, these externalities not only deteriorate the aesthetics of the city, but also have a negative impact on urban sustainability, by compromising the harmonious integration of infrastructures with the natural environment. Likewise, it negatively affects the quality of life of the citizens of Iquitos. Residents report that these types of facilities contribute to a feeling of insecurity, increase visual stress and limit urban mobility. These combined factors deteriorate the general well-being of the population, generating a less healthy and less attractive urban environment. It is evident that there is an urgent need to modernize these facilities in Iquitos, especially through underground wiring, as a viable solution to mitigate the negative externalities of overhead wiring. The willingness of citizens to contribute financially to this modernization highlights the urgency of adopting measures that improve the safety, aesthetics and sustainability of the city. But they recognize that the current management of overhead wiring by local authorities and public service companies is perceived as insufficient by the community. This lack of action and effective response has generated a widespread feeling of dissatisfaction